(3fMh GdbdhHs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdCSJGP CHh GdbGSe GdfMh(B: (3gh GdbUO Edi UhGH GdcdGe afMh GdbdhH (B: (3GdbUO Edi MejO Gdbhd HGdbdH s
(3BNQgG (B:s
(3agPg aUhd ai fMh GdbdhH CfTCJgG Ydi hLg GdEjLGR , hHGddg Jhajb GdNdb CLeYjf hYdjg GdJcdGf , hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B235 - (3U(B245s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG ebGHdI hJUMjMs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs